Are there any differences between antagonist administration on days <6 and ≥6 of Controlled Ovarian Hyperstimulation on assisted reproductive technique outcomes?. Issue 1 (January 2018) - Inal, Zeynep Ozturk; Yilmaz, Nafiye; Inal, Hasan Ali; Hancerliogullari, Necati; Coskun, Bugra
Abstract : Background: : The aim of this study was to investigate the cost‐effectiveness of antagonist administration on stimulation on days <6 and ≥6 of COH on assisted reproductive technique (ART) outcomes. Methods: : In this retrospective cohort study, 412 patients who were admitted to the ART Department were evaluated. In group 1 (203 patients), antagonist administration was provided on days <6 of COH. For group 2 (209 patients), antagonist administration was provided on days ≥6 of COH. We preferred a flexible antagonist protocol in clinical practice and added an antagonist treatment regimen when dominant follicles were enlarged to 13 mm or the serum blood E2 was >300 pg/mL. Results: : There were no differences between antagonist administration on days <6 and days ≥6 of COH in terms of age, BMI, duration and etiology of infertility, AFC, serum FSH, LH, peak E2 levels, the number of MII oocytes, 2PN, FR, the number of transferred embryos, and CPR per woman. However, there were statistically significant differences between the duration of stimulation, the total gonadotropin dose required, and progesterone levels on day hCG [8.26 ± 1.83 vs 9.56 ± 1.51 ( p = 0.001); 2173.71 ± 860.00 vs 2749.17 ± 1079.51 ( p = 0.001); 0.75 ± 0.44 vs 0.92 ± 0.59 ( p = 0.002), respectively]. Conclusion: : Our results have demonstrated that there was no effect of antagonist administration on days <6 and ≥6 of COH on ART outcomes. However, taking cost‐effectiveness into consideration, we suggest an antagonist administration on days <6 of COH since the necessary gonadotropin dose is lower.